Aplicación del modelo respuesta anticipada a situaciones anormales (RASA) a los escenarios de desastre declarados por la refinería de Barrancabermeja, partiendo de la metodología Bow Tie: caso estudio: escenario de desastre por pérdida de contención y fuga de etileno líquido en el tanque criogénico K-4102 (2020)
History has shown us the vulnerability that exists worldwide in all industrial processes and not only due to natural phenomena. Every time a disaster scenario materializes, generated by the loss of control in the operations carried out in these industrial processes, the economic losses are high, not to mention the number of human lives lost there and the potential for lead to the definitive non-continuity of these businesses. Reducing human error and ineffective human intervention represents one of the industry's greatest challenges today. In Colombia, national legislation has established a series of guidelines to properly manage industrial processes and avoid the materialization of scenarios that have the potential to generate disasters (Law 1523 of 2012 and Decree 2157 of 2017). Based on the above and in order to increase safety in operations, protect people's lives, guarantee the protection of the environment, infrastructure and, in general, safety in the environment, the Barrancabermeja refinery carried out the characterization, assessment and definition of the scenarios that have the potential to generate disaster risk, derived from the activities carried out within its facilities, and from this it built the Anticipated Response to Abnormal Situations (ARAS) model based on the Bow Tie methodology, through which compliance with the processes is ensured: knowledge and risk reduction, and emergency management. This work is focused on the development of the Anticipated Response to Abnormal Situations model for one of the scenarios of the Barrancabermeja refinery that have the potential to generate disasters, due to the loss of containment in the ethylene storage tank K-4102.